PATH-40. SPORADIC NF2 WILD-TYPE MULTIPLE MENINGIOMAS HARBOR DISTINCT DRIVER MUTATIONS. (12th November 2021) - Prilop, Insa; Pinzer, Thomas; Cahill, Daniel; Brastianos, Priscilla; Schackert, Gabriele; Juratli, Tareq
Abstract: OBJECTIVE: Multiple meningiomas (MM) are rare and present a unique management challenge. While the mutational landscape of single meningiomas has been extensively studied, understanding the molecular pathogenesis of sporadic MM remains incomplete. The objective of this study is to elucidate the genetic features of sporadic MM. METHODS: We identified nine patients with MM (n=19) defined as ≥2 spatially separated synchronous or metachronous meningiomas. We profiled genetic changes in these tumors using next-generation sequencing (NGS) assay that covers a large number of targetable and frequently mutated genes in meningiomas including AKT1, KLF4, NF2, PIK3CA/PIK3R1, POLR2A, SMARCB1, SMO, SUFU, TRAF7, and the TERT promoter. RESULTS: Most of MM were WHO grade 1 (n= 16, 84.2%). Within individual patients, no driver mutation was shared between separate tumors. All but two cases harbored different hot spot mutations in known meningioma-driver genes like TRAF7 (n= 5), PIK3CA (n= 4), AKT1 (n= 3), POLR2A (n=1) and SMO (n= 1). Moreover, individual tumors differed in histologic subtype in 8/9 patients. The low frequency of NF2 mutations in our series stands in contrast to previous studies that included hereditary cases arising in the setting of neurofibromatosis type 2 (NF2). CONCLUSIONS: Our findings provide evidence for genomic inter-tumor heterogeneity and an independent molecular origin of sporadic NF2 wild-type MM. Furthermore, these findings suggest that genetic characterization of each lesion is warranted in sporadic MM.